Periodontal Status Among Schoolchildren in the Republic of Moldova: A Cross-Sectional Study Using the Pathfinder Study Design - Leon Bilder; Elena Stepco; Diana Unkuta; Harold Sgan-Cohen; Dror Aizenbud; Amir Bilder; Eli E. Machtei (Elsevier, 2021)
Objectives: To screen a sample of Moldavian schoolchildren to establish their periodontal condition using the Pathfinder study design of the World Health Organization (WHO). Methods: Two cohorts - 12- and 15-year schoolchildren - were screened in 12 schools around the country: four schools in the capital city; four more schools in two other larger cities (two schools in each city); and four village schools (one school in each village). In addition to demographic data, the periodontal parameters dental plaque, calculus and bleeding on probing (BOP) were collected. Periodontal pocket depth (PPD) was also measured but only in the cohort of 15-year-old schoolchildren. Measurements were recorded for the six Ramfjord index teeth. Results: In total, 720 children were surveyed: 365 (50.7%) were 12 years of age and 355 (49.3%) were 15 years of age; 351 (48.8%) were girls and 369 (51.2%) were boys; 490 (68%) lived in an urban area and 230 (32%) lived in a rural area. Only 4.5% of 15-year-old children presented with a pocket depth of ≥3.5 mm. Children who lived in rural areas had higher plaque scores than children who lived in urban areas (64.8% vs. 54.1%, P = 0.007). In addition, children who lived in urban areas had significantly less calculus (P = 0.047) and shallower PPDs (P = 0.019). Deeper PPD was associated with higher PI and calculus scores. Conclusions: Moderate-to-deep periodontal pockets were not uncommon in children in the 15-year-old cohort. Periodontal status was worse in children from rural areas than in children from urban areas. It is therefore suggested that an educational programme, together with preventive and interceptive protocols, should be adopted in early adolescence and especially in rural regions.